Neurologists’ perspectives on management challenges and mitigation strategies for Parkinson’s disease patients: A qualitative study in Iraq - Mena Khalid Ibrahim; Samer Imad Mohammed; Gheyath Abd Ali Shallal Al-Gawwam (PLoS ONE, 2025)
Background Parkinson’s disease (PD) is currently the fastest-growing neurological disorder in the world. Patients with PD face numerous challenges in managing their chronic condition, particularly in countries with scarce healthcare infrastructure. Objective This qualitative study aimed to delve into neurologists’ perspectives on challenges and gaps in the Iraqi healthcare system that influence the management of PD, as well as strategies to mitigate these obstacles. Method Semi-structured interviews were conducted with neurologists from five different Iraqi provinces, working in both hospitals and private neurology clinics, between November 2024 and January 2025. A thematic analysis approach was employed to identify the main challenges and gaps in the healthcare system, along with potential mitigation strategies for improving PD management in Iraq. Results Fourteen neurologists participated in this study. Among them, 71.4% identified medication adherence as a major challenge, followed by motor symptoms (64.3%). Physical dependency due to motor impairment was the most reported limitation affecting daily life and disease management. Neurologists cited several factors influencing patients’ knowledge, including educational background, depression or family support, were mentioned by neurologists. Significant gaps in the Iraqi healthcare system were noted, such as the lack of specialized abnormal movement disorders clinics, multidisciplinary collaboration, a universal healthcare system, insufficient public PD awareness, and the presence of unregulated pharmaceuticals in the market. Conclusion Addressing these challenges requires policy-driven reforms, enhanced regulatory oversight and the integration of multidisciplinary care frameworks to optimize the management of individuals with PD. Strengthening patient education and professional training programs could further raise public awareness and improve care quality. Future research should focus on evaluating the effects of these proposed interventions on clinical outcomes for PD patients and promoting more patient-centered care for individuals with PD in Iraq.